Saturation of superconductivity in cuprates overdoped with high-pressure oxygen: Phase diagram with YBa 2 Cu 3 O 7+δ , δ → 1 - Steven D. Conradson; Luiz M. Dezaneti; Gianguido Baldinozzi; Linda Sederholm; Maarit Karppinen; Luis Casillas-Trujillo; Matthew Latimer; Oliver Mueller; Edmondo Gilioli; Alan R. Bishop; Xiaofeng Guo; Juejing Liu; et al. (Proceedings of the National Academy of Sciences, 2026)
High temperature superconductivity (HTSC) typically occurs as a “dome” over a narrow range of doping in its phase diagram. The reaction of YBa 2 Cu 3 O 7 with Ag 2 O 2 at ≥800 °C and 6 GPa inserts oxygen atoms between the Cu1 sites to form tetragonal YBa 2 Cu 3 O 8 without significant changes to its overall structure or interatomic distances. The superconductivity in YBa 2 Cu 3 O 8 is essentially unaffected, with the reduction of the transition temperature by ≤2 K and its superconducting fraction by ≤ 15% between the O7 and O8 endpoints of the oxygen stoichiometry and associated carrier density. The dome therefore only pertains to compounds doped by cation substitution or presumably interstitial oxygen. Band structure calculations of the fully ordered endpoints show substantial changes in the density of states at the Fermi level because of its shift to lower energy with increasing oxygen stoichiometry. The coincidence of optimum and saturation HTSC at a carrier:CuO 2 ratio of ≈1/6 implies a direct coupling of HTSC with the lattice such that this value is intrinsic to the superconducting phase. The SC in YBa 2 Cu 3 O 8 is therefore not only pinned at its optimum values but also separated from the other electronic states so that the additional holes have no measurable effect on the condensate. In addition, the 95 K transition temperature of Sr 2 CuO 3.4 that possesses CuO 1.5 ladders instead of CuO 2 planes reveals a second distinct behavior of cuprates overdoped with high-pressure oxygen, demonstrating significant gaps in our understanding of HTSC.